Strategy to Determine the Priority of Teachers' Quality Problem Using USG (Urgency, Seriousness, Growth) Matrix - Nova Syafira Ariyanti; Maulana Amirul Adha; Raden Bambang Sumarsono; Sultoni Sultoni (International Research-Based Education Journal, 2020)
The purpose of this study is to know, (1) identify the problem of teachers’ and educational personnel, (2) the application of USG matrix method, and (3) the impact of the problems of the educator components and education in learning at integrated islamic primary school. The method used in this study is qualitative descriptive. The research performs analysis using the matrix theory Urgency, Seriousness and Growth (USG). The site of this research is at SD Islam Terpadu Robbani Malang Regency, Indonesia. Data collection techniques with in-depth interviews, documentation, and library studies. The analysis of the data in the get resulted in the findings that correspond to the problems faced by the school. The results of the study are (1) problems that cause low PTK (Teachers and Educational Personnel) values i.e. teacher qualifications are not appropriate, teachers do not have a certificate of teachers’, and teachers do not teach in accordance with educational background, (2) problems that must be resolved in advance that (a) the teachers do not teach in accordance and (b) learners are lacking in receiving learning.